INTERPRETASI AKUSTIK IMPEDANSI (AI) MENGGUNAKAN DATA SEISMIK DAN DATA SUMUR UNTUK MENENTUKAN ZONA PROSPEK HIDROKARBON - Hanum Eko Hapsari; Intan Lestari; Samsidar Samsidar (Universitas Riau, 2018)
Research has been conducted to determine the prospect of hydrocarbon zones using the interpretation of acoustic impedance (AI) seismic method in Field X, South Sumatra Basin, Jambi Province. The purpose of this study was to determine the AI value on the distribution map of AI values for hydrocarbon prospect zones in Field X. In this study the data used were 3D seismic data with PSTM (Post-Stack Time Migration) type, and well data. Data processing using Hampson and Russell (HRS) software used in the mining and petroleum fields has a function for subsurface modeling below the ground surface of reservoir characterization. Well data will be linked to seismic data so that the well data will be in the actual position. The distribution of hydrocarbon prospect zones in PEV-1 well can be seen first in crossplot analysis at a depth of 1760-1798 m with AI cutoff value indicated as sandstone ranging from 8450 (m s)*(g/cc) and above, with a high correlation value 0.818 time shift 0 ms. Picking horizon is carried out to determine the target zone layer and its continuity laterally on seismic volume so that a model based can be done as an initial subsurface description below the soil surface at PEV-1 well. Then the next step is a post-stack analysis based model to find out how much the error value of the target zone prediction with certain parameters through the PEV-1 well data. So with a correlation value of 0.936429 and an error value of 0.35227 in the post-stack analysis model based, AI inversion in the PEV-1 well layer which is the target zone of the hydrocarbon prospect is indicated by the range of 8450 (m/s)*(g/cc) which is indicated as sandstone.